Intravenous immunoglobulin treatment improves multiple neuropsychiatric outcomes in patients with pediatric acute-onset neuropsychiatric syndrome - Eremija, Jelena; Patel, Sanjay; Rice, Sydney; Daines, Michael (Frontiers in Pediatrics, 2023)
Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS) is defined by acute onset of diverse neuropsychiatric manifestations, presumably in the setting of underlying immune dysfunction. We used standardized neuropsychological testing to assess how intravenous immunoglobulins (IVIG) impact neurological and cognitive functions in PANS patients by comparing pretreatment with post-treatment scores. A 5-year retrospective study was undertaken in Children's Postinfectious Autoimmune Encephalopathy Center at University of Arizona. We identified 12 children diagnosed with PANS and treated with immunomodulatory IVIG doses, who also completed neuropsychological testing before and after treatment. We tracked multiple patient characteristics, type/timeline of testing, and number of IVIG courses. Score change of 1 standard deviation in any tested domain/subdomain was considered improvement. We further reviewed records for laboratory signs of triggering infection and immune dysfunction. Improvement occurred in 11/12 patients, in one or multiple domains/subdomains, independently of time between disease onset and IVIG initiation (0-7 years). Participants received 1-7 IVIG courses. Improvement was primarily seen in memory (58%), sensory-motor (37%) and visual-motor integration (30%). In 5/12 patients we detected hypogammaglobulinemia requiring ongoing IVIG replacement, one patient had isolated low IgA. Only one patient had to discontinue IVIG therapy due to severe adverse effects. Standardized neuropsychological testing represents an important tool to objectively measure improvement in PANS patients. IVIG was tolerated well and showed efficacy in the vast majority of participants, independently from timelapse since disease onset, emphasizing impact of immunomodulation in PANS. Significant presence of baseline hypogammaglobulinemia in children with PANS emphasizes the presumed role of immune dysfunction in disease pathogenesis.